Munāsabah al-kitāb Durūs al-Lughah al-‘Arabiyyah al-Juz’ al-Awwal bi-asās Naẓariyyah Majlis al-Waṭanī li-Ma‘āyīr al-Ta‘līm (BSNP) - Intan Salsabila; Lailatul Qomariyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
The text book is one of the most important means when teaching the Arabic language. Therefor the teacher must have knowledge about the contents, language, presentation and graphic of the text book based on the theory of the National Board of Education Standards (BSNP). And the analysis of the text book was important to know the appropriateness of the text book because the system established by the Minister of Education and Culture that in the textbook standards including appropriate content, language, presentation and drawing graphics. The research questions of this research are: 1) How does the contents in the textbook fit the Arabic language lessons part one based on the theory of the National Board of Education Standards (BSNP)? The method of this research is the natural research, and to collect the verses by the method of documentation, and analyze them by the method of content analysis (Content Analysis). As for the results of this scientific research, it can be summarized as follows: 1) The contents were appropriate with the main competency, the basic competence, the accuracy of the materials, the renewal of the materials, the cultural suitability, the training, and the enrichment match.